THE KEY DRIVERS OF BANKS E-RECRUITMENT IN MANADO - Kalangi, Keita Ch. M.; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2014)
Internet has linked most of the countries in this whole world. It is now becoming a critical communications tools and services, with distinct characteristics and communication capabilities that allow an organization or company to use them to achieve multiple communication goals. The objective of this research is to analyze how the key drivers of e-recruitment affect recruitment methods of Banks in Manado. This research is limited to three of Development Banks that are Bank Sulut, Bank Negara Indonesia, and Bank Rakyat Indonesia as Limited Companies that using online system to recruit the right employee from ramdom candidates. Method of Analysis used in this research is quanlitative method that aimed at making valid inferences from the often overwhelming amount of collected data. The implementation of e-recruitment system for recruiting new employees in observed bank in this research has made the recruitment system become beneficial in each bank. To conclude, related with the performance of these banks, the human resources department must consider about the importance of the key drivers because of these factors roles in stimulating the management parties of these banks to execute e-recruitment system in more effective and efficient way. Keywords: internet, e-recruitment, key drivers,bank recruitment.